Integração de mídias no piloto do programa de formação continuada de professores em mídias na educação - Gomes, Paulo Marinho (2008)
This research makes a case study of Pilot Course of Continuous Formation in Education Media at Alagoas, analyzing the results of conclusion projects of students from observation of activities, knowledge and talking from students in a semi-structured interview, with the purpose of research the Media Integration. The theoretical reasons showed is technology integration between technologies of Information and communication in teachers training and teaching practice doing an analysis of public policies in EAD teaching training and describing the Pilot Project. It consolidates itself with the presentation of search results characterizing the project as relevant in the context of continuing training and media integration. Keyword: EAD Teaching Formation; Education Media; Media Integration.